Signaling Modulation by miRNA-221-3p During Tooth Morphogenesis in Mice - Aryal, Yam Prasad; Kim, Tae-Young; Lee, Eui-Seon; An, Chang-Hyeon; Kim, Ji-Youn; Yamamoto, Hitoshi; Lee, Sanggyu; Lee, Youngkyun; Sohn, Wern-Joo; Neupane, Sanjiv; Kim, Jae-Young (Frontiers in Cell and Developmental Biology, 2021)
miRNAs are conserved short noncoding RNAs that play a role in the modulation of various biological pathways during tissue and organ morphogenesis. In this study, the function of miRNA-221-3p in tooth development, through its loss or gain in function was evaluated. A variety of techniques were utilized to evaluate detailed functional roles of miRNA-221-3p during odontogenesis, including in-vitro tooth cultivation, renal capsule transplantation, in situ hybridization, real-time PCR, and immunohistochemistry. Two-day in-vitro tooth cultivation at E13 identified altered cellular events, including cellular proliferation, apoptosis, adhesion, and cytoskeletal arrangement, with the loss and gain of miRNA-221-3p. qPCR analysis revealed alterations in gene expression of tooth-related signaling molecules, including β-catenin, Bmp2, Bmp4, Fgf4, Ptch1, and Shh, when inhibited with miRNA-221-3p and mimic. Also, the inhibition of miRNA-221-3p demonstrated increased mesenchymal localizations of pSMAD1/5/8, alongside decreased expression patterns of Shh and Fgf4 within IEE in E13+2d in-vitro cultivated teeth. Moreover, one-week renal transplantation of in-vitro cultivated teeth had smaller tooth size with reduced enamel and dentin matrices, along with increased cellular proliferation and Shh expression along the HERS, within the inhibitor group. Similarly, in three-week renal calcified teeth, the overexpression of miRNA-221-3p did not affect tooth phenotype, while the loss of function resulted in long and slender teeth with short mesiodistal length. This study provides evidence that a suitable level of miRNA-221-3p is required for the modulation of major signaling pathways, including Wnt, Bmp, and Shh, during tooth morphogenesis.